APPLICATION OF THE THREE ROTHMAN EMPOWERMENT MODELS IN COMMUNITY EMPOWERMENT ACTIVITIES BY THREE NGOs IN WEST SUMATERA - Azhima, Miftah Nurul; Elfitra, Elfitra; Indraddin, Indraddin (Jurnal Mamangan, 2022)
The NGO certainly has its own way of carrying out community empowerment activities. When asked what model of empowerment was used by the three NGOs in West Sumatra, they basically built all the empowerment models, including the Rothman Empowerment model. After further investigation, the application of the Rothman empowerment model to the empowerment program carried out by NGOs was not fully implemented by the NGOs Jemari Sakato, YCM-M and LP2M. The three NGOs only used several indicators of the Rothman empowerment model in the empowerment program carried out by the NGO. For this reason, it is necessary to explain how the application of the Rothman empowerment model was carried out by the three NGOs considered that not all indicators of the empowerment model could be realized by NGOs. The purposes of this research were to describe the implementation of Rothman’s Model on every empowerment program which held by the NGOs. To describe the data collected, the researcher uses the perspective “Rothman's Three Models of Community Organizing”. This Researched used qualitative approach. The selection of informants was done by using purposive sampling technique and data collected techniques with in-depth interviews, observations, and document studies. The results from this research are the NGO of Jemari Sakato used Locality Development as its model of Rothman, YCM-M used Social Planning model of Rothman, and LP2M used Social Action Model of Rothman with nine indicators. This research has never been done before by other authors